Small-grained detector of ionizing radiation based on ZnSe(Te) - Volkov, V.G.; Gavrilyuk, V.P.; Galchinetskii, L.P.; Grinyov, B.V.; Katrunov, K.A.; Ryzhikov, V.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
A highly efficient ZnSe(Te) scintillation detector combined with Si-photodiode has been developed. A conglomerate made up of ZnSe(Te) grains is used as a scintillator. Optimal shape of the grains, reflecting cover and disperse environment type are selected to improve light collection within the detector using numerical simulation. Various shapes of light guides have been considered to maximize light output of the detector.